What Makes People With Chronic Illnesses Discontinue Treatment? A Practice Theory Informed Analysis of Adherence to Treatment among Patients With Drug-Resistant Tuberculosis in Pakistan - Shazra Abbas; Michelle Kermode; Mohammad Dost Khan; Justin Denholm; Hamed Adetunji; Sumit Kane (Kerman University of Medical Sciences, 2023)
Background  Non-adherence to treatment is a frequently observed phenomenon amongst those on long-term treatment for chronic illnesses. This qualitative study draws upon the tenets of 'practice theory' to reveal what shapes patients' ability to adhere to the demanding treatment for drug-resistant tuberculosis (DR-TB) at three treatment sites in KhyberPakhtunkhwa (KP) province of Pakistan.Methods  This qualitative study involved observation of service provision over a period of nine months of stay at, and embedment within the three treatment sites and in-depth interviews with 13 service providers and 22 patients who became non-adherent to their treatment.Results  Consistent with the extensive research based on the barriers and facilitator approach, both patients, and providers in our study also talked of patients' doubts about diagnosis and treatment efficacy, side-effects of drugs, economic constraints, unreliable disbursements of monetary incentive, attitude of providers and co-morbidities as reasons for nonadherence to treatment. Applying a practice theory perspective yielded more contextualised insights; inadequate help with patients' physical complaints, unempathetic responses to their queries, and failure to provide essential information, created conditions which hindered the establishment and maintenance of the 'practice' of adhering to treatment. These supply-side gaps created confusion, bred resentment, and exacerbated pre-existing distrust of public health services among patients, and ultimately drove them to disengage with the TB services and stop their treatment.Conclusion  We argue that the lack of supply-side 'responsiveness' to patient needs beyond the provision of a few material inputs is what is lacking in the existing DR-TB program in Pakistan. We conclude that unless Pakistan's TB program explicitly engages with these supply side, system level gaps, patients will continue to struggle to adhere to their treatments and the TB program will continue to lose patients. Conceptually, we make a case for reimagining the act of adherence (or not) to long-term treatment as a 'Practice.'